Analysis of the impact of an operator’s workstation on the safety of functioning of selected road transport systems - Muślewski Łukasz (MATEC Web of Conferences, 2019)
Modern times are characterized by fast economic and social development. However, not all spheres of life have developed in a sustainable manner, for example some elements of anthropotechnical systems are still far from being sustainable. This results in low safety level of these systems involving high risk of injury or death caused by road accidents. Transport systems of the type Human-Machine-Environment <H-M-E>, where undesired events are caused by human behavior, belong to such systems. The author of this study has addressed the issues connected with the impact of man-made objects on their operation safety. The objects in question are selected transport systems and the study subject is assessment of the equipment operator’s behavior. The main goal of this study is to provide assessment and analysis of the impact of transport means ergonomics on the quality of transport services they provide. The research object are delivery trucks with the maximum vehicle weight up to 3.5t. The first part of the study contains identification of the factors and threats which affect functioning of transport systems. Further, ergonomics criterion is defined and the factors affecting ergonomics of selected transport means are provided. A questionnaire survey was performed with participation of professional drivers who were asked to identify the factors which have an adverse effect on the safety of the transport process as well as factors that increase the drivers’ comfort of work. Basing on this, an analysis of the results was performed and negative aspects involved in driving ergonomics were identified.